The Polar Express : The Journey begins - Richards, Kitty (U.S.A : Warner Bros, 2004)
A Boy who is eagerly awaiting a visit from santa claus accepts a ride on a magical train headed for the north pole.
Keywords: Christmas- fictions; Railroads - Trains - Fiction